2008
DOI: 10.1080/00207540600957381
|View full text |Cite
|
Sign up to set email alerts
|

Master production schedule time interval strategies in make-to-order supply chains¶

Abstract: While the literature primarily addresses MPS design from the manufacturer's perspective, this research considers MPS policy design in a two-stage rolling schedule environment with a particular focus on the policy governing schedule flexibility in the non-frozen time interval (i.e. liquid versus slushy orders). Using computer simulation, we experimentally evaluate the impact of four MPS design factors (non-frozen interval policy, planning horizon length, frozen interval length and re-planning frequency) and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 50 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Over the period, it has been proven that having suppliers who provide high-quality products with minimum cost positively affects manufacturing and SCP (John et al, 2006;Beamon, 1999;Kannan and Tan, 2005). Several studies showed that the effective use of the master production schedule is very important for better manufacturing performance (Gunasekaran et al, 2001;Bhagwat and Sharma, 2007;Robinson et al, 2008;Cho et al, 2012).…”
Section: Manufacturing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the period, it has been proven that having suppliers who provide high-quality products with minimum cost positively affects manufacturing and SCP (John et al, 2006;Beamon, 1999;Kannan and Tan, 2005). Several studies showed that the effective use of the master production schedule is very important for better manufacturing performance (Gunasekaran et al, 2001;Bhagwat and Sharma, 2007;Robinson et al, 2008;Cho et al, 2012).…”
Section: Manufacturing Processmentioning
confidence: 99%
“…Several studies showed that the effective use of the master production schedule is very important for better manufacturing performance (Gunasekaran et al. , 2001; Bhagwat and Sharma, 2007; Robinson et al. , 2008; Cho et al.…”
Section: Literature Review and Supplier Selection Frameworkmentioning
confidence: 99%
“…They conducted full-factorial experiments to define the main drivers of MPS policy cost and schedule stability. Powell Robinson, Sahin, and Gao (2008) also develop a two-stage rolling schedule environment with a particular focus on the policy related to the schedule flexibility in the non-frozen time intervals [26]. Sawik (2007) explored the same topic by developing multi-objective, long-term production scheduling in an MTO environment and a lexicographic approach with a hierarchy of integer programming formulations [27].…”
Section: Literature Reviewmentioning
confidence: 99%